Membangun Nasionalisme Generasi Z melalui Dialog Intergenerasi dan Media Digital Berbasis Nilai Lokal di Desa Bioa Sengok - Muhammad Fauzan Aziman; Yogopriyatno, Jatmiko; Susanti, Is; Fariz Antonius Azhari (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This community service program aims to develop a model for strengthening Generation Z nationalism through integration of intergenerational dialogue with digital media based on local values in Bioa Sengok Village, Lebong Regency, Bengkulu. This village is a remote rural area in Sumatran highlands with mountainous topography and limited infrastructure access. Partner problems include low understanding of national values among Gen-Z, lack of intergenerational dialogue spaces, and suboptimal use of digital media in the context of digital divide due to mountainous topography. Participatory action research methods were applied involving 25 Gen-Z participants through interactive dialogue series, digital content production workshops, and development of "Nusantara Digital" offline learning platform. Evaluation results show significant increase in understanding of national values by 29% (from average 66.3 to 85.5), formation of 10 trained local facilitators, and creation of 35 educational digital contents. Research novelty lies in intergenerational dialogue approach as bridge for transferring local wisdom to internalization of national values, combined with offline digital platform addressing digital divide constraints in remote mountainous regions.